Design and Build a Covid-19 Health Protocol Tool at a Doctor's Practice Based on the Internet of Things - Siti Nur Sakinah; William Ramdhan; Sumantri Sumantri (Universitas Budi Darma, 2022)
Since the beginning of 2020, the world has been facing an outbreak of the Corona Virus Disease (COVID-19). A person can catch the Corona virus when touching the nose, mouth or eyes after touching a surface that has been contaminated with the virus from a person who coughs or sneezes. To prevent contracting COVID-19, one way that can be done is to get used to washing hands with soap and running water, especially when in public places. Doctor Usman's practice is one of the medical practices in Kisaran City. The doctor's practice handles common diseases, the patients who come consist of various groups. During the current pandemic, the existing health protocols are strictly guarded in order to stop the spread of the existing virus. The protocol used is to always wear a mask, keep a distance and wash your hands before entering. Hand washing in practice is still using manual hand washing, namely with water filled in a paint barrel and given a faucet. The working system of the tool made is when the patient's hand is close to the water faucet, the ultrasonic sensor will detect the distance between the sensor and the hand. When the detected distance is less than the specified distance, the relay will be active to order the water out. The working system for soap and hand dryers is also the same as for water systems, namely detecting with an ultrasonic system. Then when the water sensor located in the water and soap container detects that the contents are empty, the sensor in it sends a notification to the officer or nurse who is in charge of the tool. With the automatic hand washing device, people don't need to touch the water faucet to wash their hands, thereby minimizing the possibility of transmitting the virus